2022
DOI: 10.3390/jcm11133708
|View full text |Cite
|
Sign up to set email alerts
|

Femoral and Lateral Femoral Cutaneous Nerve Block as Anesthesia for High-Risk Intertrochanteric Fracture Repair Patients

Abstract: Introduction. Intertrochanteric fracture (IF) is a common injury among the elderly. Due to significant comorbidities, anesthesia for IF repair may be challenging. The authors propose femoral nerve block together with a lateral femoral cutaneous nerve block and sedation as an anesthetic technique for most severe cases of IF with contraindications to spinal anesthesia. Methods. In total, 61 patients were enrolled prospectively in a study, 19 received general anesthesia (GA group), 22 spinal anesthesia (SA group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…The LFCN block was again studied as a part of a primary anesthetic, this time with the FNB as the other half, in hip fracture patients with a high co-morbidity load. The authors found the combination of blocks to be sufficient to get the patient through intramedullary nail placement as a salvage anesthetic when spinal or GA is not appropriate [ 22 ].…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…The LFCN block was again studied as a part of a primary anesthetic, this time with the FNB as the other half, in hip fracture patients with a high co-morbidity load. The authors found the combination of blocks to be sufficient to get the patient through intramedullary nail placement as a salvage anesthetic when spinal or GA is not appropriate [ 22 ].…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%